SAFER DIGITAL SPACES FOR CHILDREN: INTEGRATING FAMILY GUIDANCE AND TECHNOLOGICAL SAFEGUARDS - Madina , Eshboyeva; Temur , Eshboyev; Bultakov , Sardor (Scientific practical conference, 2026)
The rapid expansion of digital platforms has transformed childhood socialization, learning, and communication. While virtual environments provide educational and creative opportunities, they also expose minors to algorithmic risks, privacy threats, and harmful content. This paper examines child online safety from a computer science perspective, emphasizing AI-driven content systems, cybersecurity risks, and protective mechanisms. It proposes an integrated framework combining safety-by-design technologies, digital literacy, parental mediation, and regulatory safeguards. The study argues that responsible algorithm design and collaborative governance are essential for ensuring safe digital environments for children.